The Effect Of Reality Group Counseling With The Wdep Technique In Increasing Adolesceny Social Responsibility - Sulistiyowati, Linda; Tawil, T; Yuhenita, Nofi Nur (Prosiding University Research Colloquium, 2021)
This study aims to examine the effect of group counseling techniques WDEP towardsincreasing the social responsibility of youth in Sokorini Village, Muntilan, Magelang.In this research is a type of research Pre-experiment by using design One Group PretestPosttest Design. The design uses one group of subjects with one type of treatment, namelythe experimental group. The population in this study were Sokorini teenagers, whichconsisted of 15 teenagers. The number of samples in this study were 7 teenagers who hada score ofpretest low and medium categories. Determination of sampling using analysispurposive sampling, namely the determination based on the goals or characteristics thathave been determined. The analytical method in this study uses parametricPaired samplet-testThe results of this study indicate that technical group counseling WDEP positive effect onincreasing adolescent social responsibility. This is evidenced by the test resultspairedsample t-test with a significant 2-tiled 0.001<0,05. And based on the results of theanalysis and discussion, there is a difference in the average score of the adolescent socialresponsibility questionnaire of 29.02% from the resultspretest and result posttest youthsocial responsibility questionnaire.